2020
DOI: 10.18203/2349-2902.isj20205355
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of laparoscopic versus open appendectomy for the treatment of acute appendicitis

Abstract: Background: Acute appendicitis is one of the most commonly encountered emergency by the general surgeons and appendectomy is the most common surgery performed in the world. Although open appendectomy is preferred by many surgeons, yet the laparoscopic approach is gradually replacing open surgery for treatment of acute appendicitis.Methods: A total of 400 patients of acute appendicitis were operated, 200 by laparoscopic appendectomy and 200 by open method by a single surgeon at various private hospitals in Jamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Our findings were supported by Singh et al 3 Our findings were supported by Resutra and Gupta 14 as they reported that 160 (80%) of the patients in Group A were completely satisfied with the scar and aesthetic result, 30 (15%) were moderately satisfied, and 10 (5%) were dissatisfied owing to the bad scar.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings were supported by Singh et al 3 Our findings were supported by Resutra and Gupta 14 as they reported that 160 (80%) of the patients in Group A were completely satisfied with the scar and aesthetic result, 30 (15%) were moderately satisfied, and 10 (5%) were dissatisfied owing to the bad scar.…”
Section: Discussionsupporting
confidence: 86%
“…15 The authors found that the mean age of studied cases was 27.41 years. Similarly, Resutra et al 16 in their study of 400 patients of acute appendicitis treated by open as well as LA found the mean age of studied cases to be 35 years.…”
Section: Discussionmentioning
confidence: 68%